How Do You Find a Good Manager? - Ben Weidmann; Joseph Vecci; Farah Said; David Deming; Sonia R. Bhalotra (Institute of Labor Economics (IZA), 2024)
This paper develops a novel method to identify the causal contribution of managers to team performance. The method requires repeated random assignment of managers to multiple teams and controls for individuals' skills. A good manager is someone who consistently causes their team to produce more than the sum of their parts. Good managers have roughly twice the impact on team performance as good workers. People who nominate themselves to be in charge perform worse than managers appointed by lottery, in part because self-promoted managers are overconfident, especially about their social skills. Managerial performance is positively predicted by economic decision-making skill and fluid intelligence – but not gender, age, or ethnicity. Selecting managers on skills rather than demographics or preferences for leadership could substantially increase organizational productivity.
Keywords: M54; J24; C90; 330; teamwork; managers; skills; measurement; experiment